FRASA PREPOSISIONAL DALAM CERPEN PILIHAN KOMPAS 2016 TANAH AIR - Trisna Budi Susanti; Mukhlish Mukhlish (Universitas Sarjanawiyata Tamansiswa, 2020)
This research aims to (1) describe the prepositions of fillers of directors in prepositional phrases in Cerpen Pilihan Kompas 2016 Tanah Air. (2) Describe the axis filler categories in prepositional phrases in Cerpen Pilihan Kompas 2016 Tanah Air. (3) Describe the prepositional phrase structure in Cerpen Pilihan Kompas 2016 Tanah Air. (4) Describe the syntactic function of prepositional phrases in Cerpen Pilihan Kompas 2016 Tanah Air. This research is qualitative research. This research data is a sentence containing prepositional phrases in Cerpen Pilihan Kompas 2016 Tanah Air.